Exploring the relationship between cycle threshold values and oral manifestations in COVID-19: a comprehensive overview - Dalit Porat Ben Amy; Hanan Rohana; Maya Azrad; Michael V. Joachim; Ori Bar; Imad Abu El-Naaj; Avi Peretz (Medical Journals Sweden, 2024)
Objective: This cross-sectional study aimed to compare oral manifestations between severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)-positive and SARS-CoV-2-negative patients and to examine associations between oral symptoms, Ct values of E and N SARS-CoV-2 viral genes, and the implications of low Ct values indicating a high viral load, which is a predictive factor for the outcome of COVID-19. Methods: A total of 353 participating patients were aged ≥18 years with clinical manifestations of COVID-19 infection and tested for SARS-CoV-2 carriage at the medical center, by reverse transcriptase polymerase chain reaction (RT-PCR). All patients filled out an anonymous digital questionnaire regarding oral and general symptoms and overall medical health.  Results: A significant association was found between SARS-CoV-2 carriage and dry mouth, unpleasant taste and changes in taste (p < 0.001); for example, 37.4% of the 147 SARS-CoV-2- positive participants had a dry mouth, compared to 18.9% of the 206 SARS-CoV-2- negative participants. Oral blisters were experienced by patients with an E gene Ct value of 10-20 (50%) or 21-30 (50%) (p = 0.041). Bad breath, dry mouth, unpleasant taste and changes in taste were mostly present in participants whose Ct values of both E and N genes were between 21 and 30.  Conclusions: This study found significant associations between low Ct values of E and N SARS-CoV-2 viral genes and high viral load, indicating that Ct values can serve as predictive factors for COVID-19 outcomes. The findings suggest that while oral symptoms are present, the Ct values and associated high viral loads are more critical indicators of disease severity and prognosis.